KEPEMILIKAN JAMINAN KESEHATAN DENGAN KEPUASAN PASIEN DI PUSKESMAS JETIS 1 BANTUL, YOGYAKARTA - Aprianus Umbu Zogara (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
Quality of service is an important thing that must be considered by every facilityof health services in providing services to patients. Quality of service is closelylinked with comprehensive and systematic services to provide excellent servicewithout distinguishing any patient either public or health-care users. The purposeof this study to determine the relationship between the ownership of healthinsurance with patient satisfaction in Puskesmas Jetis 1 Bantul, Yogyakarta. Thisresearch is a quantitative research with cross- sectional design. Samples in thisstudy were patients who came to visit or seek treatment and enrolled inPuskesmas Jetis 1 Bantul as many as 97 people taken by accidental samplingtechnique. Data were analyzed using chi-square analysis. The results showedmost of the respondents who have collateral such as Askes, JKN, Jamkesda, andJamkesmas (67%) were satisfied with the services provided. The result of chisquarecorrelation test shows that there is correlation between assuranceownership and patient satisfaction at Puskesmas Jetis 1 Bantul, Yogyakartawhich is shown by Sig value. of 0.00 (Sig <0.05).Keywords: Warranty ownership, Patients satisfaction